Mining and First Nations in Canada (Global Journal of Management and Business Research, 2015)
Decisions on a considerable number of mining projects in Canada are being affected by issues related to First Nations communities This paper will review First Nations issues with respect to resource development The historical nature of these issues is requiring mining companies to rethink how they approach mine projects especially with respect to community engagement partnership and value-sharing Examples of successful engagement and unsuccessful efforts will be presented
Keywords: mining in canada; first nations; engagement; resistance; impact-benefit-agreements